2020
DOI: 10.31491/apt.2020.03.014
|View full text |Cite
|
Sign up to set email alerts
|

The potential of GHK as an anti-aging peptide

Abstract: GHK (glycyl-L-histidyl-L-lysine) is a naturally occurring peptide found in human serum with levels averaging 200 ng/ml at age 20 but declining to an average of 80 ng/ml by age 60. The molecule has a very high affinity for copper and forms the chelate GHK-Cu. The peptide as well as its Cu (II) chelate have anti-inflammatory and tissue remodeling properties. GHK-Cu has been shown to promote skin remodeling, wound healing and regeneration, and has prominent antioxidant and anti-inflammatory effects in in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Thirdly, it has been suggested that anxiety may induce accelerated aging across multiple biological processes [35]. Recent research of cellular ageing indicates that the human plasma peptide Gly-His-Lys, which has powerful anti-anxiety effects, is related to the suppression of several molecules that favor accelerated cellular ageing [36,37]. Fourthly, anxiety is linked to elevated levels of glucocorticoids [38], which have been shown to increase cardiovascular disease risk [39], and to be associated with impaired cognitive performance [40], as well as with impaired memory retrieval and impaired working memory during emotionally arousing test situations [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, it has been suggested that anxiety may induce accelerated aging across multiple biological processes [35]. Recent research of cellular ageing indicates that the human plasma peptide Gly-His-Lys, which has powerful anti-anxiety effects, is related to the suppression of several molecules that favor accelerated cellular ageing [36,37]. Fourthly, anxiety is linked to elevated levels of glucocorticoids [38], which have been shown to increase cardiovascular disease risk [39], and to be associated with impaired cognitive performance [40], as well as with impaired memory retrieval and impaired working memory during emotionally arousing test situations [41].…”
Section: Discussionmentioning
confidence: 99%
“…Copper ions show a high affinity for the human tripeptide GHK, which regulates a large number of human genes involved in neuronal development and maintenance, which suggests the possibility of using GHK as a therapeutic target against cognitive decline and age-dependent neurodegeneration [155]. The ability of GHK to reverse, albeit partially, cognitive impairment through anti-inflammatory and epigenetic pathways has also been demonstrated in an aging mouse model [156]. Mushrooms may accumulate high levels of Zn in their fruiting body [144,[156][157][158][159][160].…”
Section: Mineralsmentioning
confidence: 99%
“…Sleep deprivation increased nitrotyrosine levels in both the CA3 and DG regions of the hippocampus, and GHK treatment successfully prevented such an effect (Figure 2B). GHK is known to work as an anti-inflammatory and antioxidant agent by decreasing inflammatory cytokines and reducing reactive oxygen species (ROS) levels [7]. Nitrotyrosine is considered a biomarker for oxidative stress as the result of…”
Section: Learning Abilitymentioning
confidence: 99%